2009
DOI: 10.1021/ie900361m
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Analysis of Possible Column Arrangements for Multicomponent Separations by Preparative Chromatography

Abstract: The optimal arrangement of eight identical chromatographic columns for the isolation of the intermediate adsorbing component of a ternary mixture is investigated theoretically. The arrangements considered are batch chromatography with columns connected in series and/or in parallel, cascades of two standard simulated moving bed (SMB) processes, and combinations of standard SMB units and batch columns. Based on standard column models, the productivity of each configuration was maximized by optimizing the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…This is the reason attaining cyclic steady-state takes several (here, four) cycles. Overall, the result appears plausible, since it is typical for such optimized scenario with limited purity requirements (see for example [11]). The fractionation of the last cycle of the optimized process is shown in Figure 6 (right).…”
Section: Case 1: Batch Chromatography For a Binary Separationmentioning
confidence: 56%
See 2 more Smart Citations
“…This is the reason attaining cyclic steady-state takes several (here, four) cycles. Overall, the result appears plausible, since it is typical for such optimized scenario with limited purity requirements (see for example [11]). The fractionation of the last cycle of the optimized process is shown in Figure 6 (right).…”
Section: Case 1: Batch Chromatography For a Binary Separationmentioning
confidence: 56%
“…Both gradient-based non-linear programming (NLP) solvers (e.g., interior-point algorithms [30], sequential programming [29], or simplex [11]) and derivative-free approaches (e.g., genetic algorithm [31] and Gaussian process regression [32]) were used successfully for optimal process design. Moreover, mixed-integer non-linear programming (MINLP) was applied to general process optimization using extended cutting plane algorithms [33], as well as for structural decision variables using outer approximation [34], and evolutionary algorithms [35].…”
Section: Process Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using such a process, not only ternary mixtures can be treated, but, more importantly, a so-called center cut separation can be performed to isolate a certain target component out of a pseudo-ternary mixture. Evidence for intensive research can be found in several publications, which suggest different configurations for solving this difficult problem [140][141][142][143][144][145][146][147][148][149][150]. However, the application of such advanced SMB processes for the separation of complex mixtures is still exceptional.…”
Section: Separation Of Ternary Mixtures: Center Cut Separationsmentioning
confidence: 99%
“…In the other hand, the use of preparative scale stands out as a versatile and fast tool capable to isolate high‐purity bioactive compounds from complex mixtures such as plant extracts . One of its fundamental characteristics is the possibility of injection of high volumes or concentrations , besides that this scale might use a high flow rate leading to a higher pressure, allowing to obtain purified compounds in a larger scale, resulting in a higher productivity and lower process costs . However, this scaling‐up should be done sparingly, since loading column capacity may affect separation performance causing compounds coelution due to the column saturation.…”
Section: Introductionmentioning
confidence: 99%